Spending Pattern among Gen X versus Gen Y in Bandung City - Putra, Nugraha Pratama; Saudi, Mohd Haizam Mohd; Razimi, Mohd Shahril Ahmad (International Journal of Psychosocial Rehabilitation, 2020)
With the aging of the Baby Boomers the generation X and Y population is getting significant importance among the researchers. Baby boomers are those who were born during 1946-1964 are approaching to their retirement age and their population is getting smaller, the children of baby boomers i.e. Gen-X and Gen-Y is the biggest group and is the main focus for the marketers and policy makers. Yet, these generations have various characteristics as compared to policy makers and their parents. Marketers are changing their strategies to accommodate these generation. This study will be helpful for the businesspeople in relation to the Gen-X and Gen-Y which will be profitable and lucrative segment for the Indonesian marketers, and they have significantly greater income to satisfy their desires and wants. The analysis done in the study has significant importance for the policy makers such as business and government in providing suitable services and products in in accordance with their spending and consumption habits.